2010
DOI: 10.1051/0004-6361/201014246
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicity of late-type B stars with HgMn peculiarity

Abstract: Context. Observations at various wavelengths of late B-type stars exhibiting strong atmospheric overabundances of the chemical elements Hg and Mn indicate that these stars are frequently found in binary and multiple systems. Aims. We intend to study the multiplicity of this type of chemically peculiar stars, looking for visual companions in the range of angular separation between 0. 05 and 8 . Methods. We carried out a survey of 56 stars using diffraction-limited near-infrared imaging with NAOS-CONICA at the V… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 48 publications
4
58
0
Order By: Relevance
“…Dolk et al (2003) reported T eff = 10 612 ± 200 K and log g = 3.79 ± 0.10 together with [Fe/H] = 0.15 from Smith & Dworetsky (1993). On the grid of stellar evolutionary tracks from Bertelli et al (2009), the three-solar-mass track with Y = 0.3 and Z = 0.017 gives the best match as far as log g and T eff are concerned (left panel of Fig.…”
Section: Astrophysical Outcomementioning
confidence: 84%
See 1 more Smart Citation
“…Dolk et al (2003) reported T eff = 10 612 ± 200 K and log g = 3.79 ± 0.10 together with [Fe/H] = 0.15 from Smith & Dworetsky (1993). On the grid of stellar evolutionary tracks from Bertelli et al (2009), the three-solar-mass track with Y = 0.3 and Z = 0.017 gives the best match as far as log g and T eff are concerned (left panel of Fig.…”
Section: Astrophysical Outcomementioning
confidence: 84%
“…The magnitudes of the two components differ by 5.7 in V and 3.9 in K. Such a large difference in V explains the absence of the signal in the Hipparcos data and in the spectra. The semi-major axis of the relative visual orbit is 36.3 mas only, making this system essentially inaccessible to VLT/NACO (Schöller et al 2010). The two components are nevertheless bright enough to be resolved with the VLTI.…”
Section: Astrophysical Outcomementioning
confidence: 99%
“…Smith & Dworetsky (1993) measured the stellar parameters of the primary component and found T a = 10 750 K and log(g a ) = 4.0. Wahlgren et al (1994) iteratively determined the parameters of the two components by a detailed spectroscopic modeling and obtained T a = 10 650 K, T b = 9200 K, log(g a ) = 3.89 and log(g b ) = 4.2.…”
Section: Temperatures Sizes and Agementioning
confidence: 99%
“…The CP stars of mercury-manganese (HgMn) type are exceptional cases where no clear magnetic field is detected but peculiarities (and sometimes spots) are still present on the stellar surface. Observations suggest a correlation between the presence of a weak magnetic field, abundance anomalies, and binary properties (Schöller et al 2010;Hubrig et al 2012). More studies of HgMn stars are especially important for understanding the role of the multiplicity and the magnetic field as well as the evolutionary aspects of the chemical peculiarity phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…These late, main-sequence B stars have effective temperatures ranging from 10 500 to 15 000 K and masses roughly between 2.5 and 5 M (e.g., Adelman et al 2003). They are also often found in binary systems (e.g., Catanzaro & Leto 2004;Schöller et al 2010Schöller et al , 2012.…”
Section: Introductionmentioning
confidence: 99%